PENGARUH CUSTOMER EXPERIENCE, WORD OF MOUTH DAN PRODUCT QUALITY TERHADAP LOYALITAS PELANGGAN (Studi kasus usaha Pempek Palembang Cek Wanda Dalung Permai, Badung, Bali) - Andrean Lukyansyah WADUN; Agus Widarko; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract In this research, the type of research used is explanatory research with a quantitative approach. This research was conducted at the location of the business food court in Pempek Palembang, Check Wanda, Dalung Permai Housing, Badung Regency, Bali Province, 80363. The technique used in this study was data collection by distributing questionnaires to business customers of Pempek Palembang Cek Wanda in Dalung Permai Housing, Badung Regency, Bali Province. The population in this study were consumers of Pempek Palembang Cek Wanda in Dalung Permai Housing, Badung Regency, Bali Province. Determination of the sample in this study using purposive sampling technique. Purposive sampling is a sampling technique with certain considerations based on criteria. The results of this study indicate that Customer Experience has no significant effect on customer loyalty, Word Of Mouth has no significant effect on Customer Loyalty, Product Quality has a significant effect on Customer Loyalty.Keywords: Customer Loyalty, Customer Experience, Word Of Mouth, Product Quality